ASURANSI KONVENSIONAL DAN ASURANSI SYARIAH: PERBEDAAN DALAM LINGKUP AKUNTANSI - Rosidah, Nur Hidayati (Jurnal Akuntansi AKUNESA, 2014)
Insurance is a form of risk control. Insurance companies take advantage of opportunities against the need for risk control. Insurance companies studied were conventional insurance and islamic insurance. Author aims to describe differences in conventional insurance and islamic insurance. Conventional insurance and islamic insurance using different accounting standards. Conventional insurance accounting using accrual basis of accounting while using the cash basis of Islamic insurance. The financial statements are presented conventional insurance and islamic insurance different.Keyword: accounting, conventional insurance and islamic insurance